(untitled) (Bangladesh Journal of Botany, 2024)
Genetic diversity was determined in 50 pearl millet germplasm accessions based on yield and yield components using multivariate diversity analysis. Cluster analysis categorized the 50genotypes in to nine clusters with largest number of genotypes (31) present in cluster I. Clusters III and VIII were identified as distantly related clusters with cluster VIII possessing maximum cluster mean value for various productive traits such as spike girth, single ear head weight, single plant yield and single ear head threshed weight. Characters such as single plant yield, plant height and single ear head weight contributed the maximum towards divergence. So these traits may be given importance for the selection of parents.PCA revealed the existence of three principal components with eigen value more than 1.0 which contributed for 86.28% of the total variability among the traits studied. Based on PCA and cluster analysis, genotypes viz., Kattu cumbu1, Kattu cumbu2, Kattu cumbu3 and PT7035 were adjudged as potential genotypes for the synthesis of heterotic hybrids. Bangladesh J. Bot. 53(4): 1035-1042, 2024 (December)